A Comparative Study of Human Reliability Assessment using Success Likelihood Index Method (SLIM) and Human Error Assessment & Reduction Technique (HEART): A case study from a Boeing 737 Max Accident - Ramdhan, M Zaki; Rizq, Daffa Abyan; Senna, Ayrton; Ramadhani, Adhitya Ryan (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2025)
The accurate assessment of Human Error Probability (HEP) is crucial for aviation safety, especially in complex systems such as the Manoeuvring Characteristics Augmentation System (MCAS). This study compares two widely used human reliability analysis methods, HEART (Human Error Assessment and Reduction Technique) and SLIM (Success Likelihood Index Method), to evaluate their effectiveness in identifying and quantifying MCAS-related human errors. The results indicate that HEART is highly sensitive to human and organizational factors, as in Error Mode 5, where the calculated HEP is 0.164. In contrast, SLIM focuses more on system design and interaction reliability, yielding a significantly lower HEP of 0.0049. The comparative analysis highlights the strengths and limitations of each method, suggesting that a hybrid approach could improve the accuracy of human error assessments in aviation, leading to more effective risk mitigation strategies.